2011
DOI: 10.7861/clinmedicine.11-3-251
|View full text |Cite
|
Sign up to set email alerts
|

Red flags in medical practice

Abstract: Oral feeding diffi culties and dilemmasA guide to practical care, particularly towards the end of life 10% discount for fellows and membersQuote the reference Clinical Medicine when making your order

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…However, some of these disease entities may exhibit unusual signs highly suggestive of a particular disease, which may serve as “red flag” signs to guide the work-up including the choice of paraclinical tests. Although the concept of red flags is intuitive for physicians ( 12 ), only one article explicitly applies it to the etiologic diagnosis of chorea syndromes ( 13 ). In addition, the specific paraclinical tests deemed necessary are sometimes unaffordable or inaccessible.…”
Section: Introductionmentioning
confidence: 99%
“…However, some of these disease entities may exhibit unusual signs highly suggestive of a particular disease, which may serve as “red flag” signs to guide the work-up including the choice of paraclinical tests. Although the concept of red flags is intuitive for physicians ( 12 ), only one article explicitly applies it to the etiologic diagnosis of chorea syndromes ( 13 ). In addition, the specific paraclinical tests deemed necessary are sometimes unaffordable or inaccessible.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we found that clinicians indicated they would order neuroimaging 67.1% of the time in scenarios with red flags that have limited evidence to support their use. The use of “red flags” to identify underlying medical conditions originated in back pain, 31,32 but has been extended to a number of settings, 33 including other neurologic conditions, such as Parkinson’s disease 34 and cauda equina syndrome 35 . In conditions other than headache, systematic reviews typically find that red flags result in low sensitivity and a high false positive rate 31,34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, as the telehealth consult progresses, it becomes evident that the patient's reason for consulting a clinician is of a complexity that exceeds the telehealth context. 9 This situation should prompt the clinician to consider if there is a need for further assistance in their patient's care in some other manner, such as moving to a face-to-face consult or seeking a second opinion from a specialist, peer or supervisor.…”
Section: Final Thoughtsmentioning
confidence: 99%